Los beneficios de la organización : la primera huelga general de los zapateros de Barcelona (mayo-agosto de 1872) - Joël Delhom (Amnis)
The first general strike of the Barcelona shoemakers took place between May and August 1872, following a national congress that agreed to found the Union of the trade, which was affiliated to the First International, and in a context of economic crisis and the transformation of modes of production. It was a response to a bosses’ lock-out aimed at nipping in the bud the organisational efforts and demands of the journeymen. As the revolutionary and apolitical class struggle orientation of the leaders was not shared by the entire trade, tensions arose among the strikers when the bourgeois press (including the federal republican press) censured the organisation of pickets to prevent scabs from entering the workplace and when the civil governor tried to mediate in the conflict. However, this strike had very positive consequences for the organisation of the shoemakers. The role of the press is another aspect of the modernity of this labour conflict.